Proposal for document management in the context of public administration - Bedoya Barco, Diana; Gasca Collazos, Lucidia; Varela Mateus, Wendy Tatiana; Cruz Castillo, Alba Lucía (Revista General de Información y Documentación, 2024)
In order to identify the problems that affect document management in the field of public administration and its impact on the correct management of the processes of territorial entities, it is pertinent to analyze the shortcomings, tensions and recurrences of document management in a case particular of the Solita Caqueté Mayor’s Office; being this the object of study of the present investigation, it was developed from a diagnostic process that allowed validating the level of compliance against the applicable current regulations, this associated to the needs and energizing the entity’s own resources, which will allow the empowerment and training of human capital an, in turn, the improvement of its processes.